Pain Management in Advanced Hepatocellular Carcinoma:A Case Study - Fitrianti, Fita; Shatri, Hamzah; Faisal, Edward; Putranto, Rud; Agung, Ratih Arianita; Nainggolan, Leonard; Kalista, Kemal Fariz; Irawan, Cophiadi (Jurnal Penyakit Dalam Indonesia, 2022)
Hepatocelullar carcinoma (HCC), the most common primary liver malignancy is the fifth most common cancer and the third most frequent cause of cancer related death globally. Pain comprises one the most common symptoms of HCC and may have severely negative effects on patient’s quality life. Furthermore, patients with HCC often presented with a cirrochis,so to control pain in this patient poses a clinical challenge. This case report discuss about a young 26-years-old male patient who presented with a four-month history of right upper quadrant abdominal pain and weight loss. HbsAg positive and serum alpha-fetoprotein level was high. Computed tomography (CT) and liver biopsy confirmed the presence of primary hepatocellular carcinoma.,with lung metastatic from the radiologic x-ray. Patient came with a loss of consciousness due to hypoglicemia. During hospitalization, patient complaint of abdominal pain and was given morphine intermediate release (MIR) to control the pain. By administering measurable and well-controlled opioids, the patient’s suffering can be reduced, thus improving the patient’s quality of life